PENGARUH KEBIJAKAN HUTANG, KEBIJAKAN DIVIDEN, CORPORATE SOCIAL RESPONSIBILITY DAN GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2017) - Fadila Nurul; Kamaliah Kamaliah; Adhitya Adhitya (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims to examine the effect of debt policy, dividend policy, corporatesocial responsibility and good corporate governance on firm value. The population inthis study were 154 manufacturing companies in the Indonesia Stock Exchange. Thisstudy uses a purposive sampling method, so there are 33 manufacturing companies listedon the Indonesia Stock Exchange in 2014-2017 that meet the sample criteria. Dataanalysis using multiple regression models. This study states that Good CorporateGovernance does not affect the value of the company. Debt policy affects the value of thecompany. dividend policy affects the value of the company. and corporate socialresponsibility affects the value of the company. This means debt policy, dividend policyand corporate social responsibility are factors that need to be used as material forconsideration in managing corporate value.Keywords : Debt Policy, Dividend Policy, Corporate Social Responsibility, GoodCorporate Governance, Firm Value